Potential of Local Currencies in the Czech Republic: DSGE model - Gawthorpe, Katerina (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The Czech Republic is an economy with one of the most municipalities per squared kilometer in Europe. The localization factor of individual municipalities causes their different reaction to exogenous shocks. The subsequent varying transmission of shocks into prices questions the convenience of the dominant position of the Czech currency for all regions. Instead, community currencies respect regional heterogeneity as well as endorse social values national currency is weak of targeting. Individuals, companies but also municipalities in other countries seem to realize these benefits of community currencies. Over four-thousands of community currencies operate worldwide. Spain belongs among one of the most recent member of such local-currency movement. High unemployment rate in Spain has motivated local activists to launch several time-banking schemes. These schemes multiplied into more than four hundred. Greece copied such effort to provide unemployed and impoverished individuals with additional means of exchange along with independence on scarce euro currency. Local currencies could help Czech Republic to respect regional discrepancies and allow local communities to be more flexible to transmission shocks and varying economic conditions. This study analyzes the benefits of such potential scenario with local currencies in the Czech Economy. The applied method represents an enhancement of the DSGE model as designed by the Ministry of Finance in the Czech Republic for local-currency variables. All set of monetary policy and fiscal policy shocks along with a shock into the local currency will allow to determine the potential importance of community currencies for the Czech Economy
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 155-168
Keywords: Local currencies; Alternative currencies; DSGE models; Czech Republic